SELF-COMPASSION TUNANETRA DEWASA: EFEK KOPING RELIGIUS DAN RASA SYUKUR - Aldyafigama, Nabila Salwa; Baihaqi, MIF; Pujasari, Yayah (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
The aim of this study was to identify the relationship of religious coping with self-compassion, gratitude with self-compassion, and the relationship of both religious coping and gratitude with self-compassion on postnatal visually impaired early adults at PSBN Wyataguna Kota Bandung. This study used quantitative method with 79 postnatal visually impaired students as participants. Iranian Religious Coping Instrument was used to measure religious coping in this study, GQ-6 instrument was used to measure gratitude, and Self-Compassion Scale was used to measure self-compassion. Data analysis technic that was used in this study was simple correlation and linear regression. Result of this study showed that religious coping and gratitude are positively correlated to self compassion with a score of 0.614.